Una breve reflexión sobre la psicología contemporánea - José Mauricio Cuartas Arias (Universidad de San Buenaventura, 2010)
Making approximations to the genealogy of subjectivity, a term coined by Michel Foucault, who in turn approached conceptually what might be considered as an “archeology of psychology” and later outlined the concept of “psychological interiority”, "which converges well with the search for the individuation process. It should be noted that currently the psychological interiority may well result from the features theory made by R. Catell and G. Allport, or perhaps the psychological interiority can be integrated from the temperament approaches suggested by R. Cloninger and have a heritable basis and that allow the consolidation of identity and personality (Celikel, Kose et al. 2009).